Applications of Cellulolytic Microorganisms and Watering Frequency in Early Seedling of Palm Oil in Peatlands - Gusmawartati Gusmawartati (Natural B, Journal of Health and Environmental Sciences, 2012)
This research aimed to determine optimum water necessity by using cellulolytic microorganism to enhance growth of oil palm on pre-nursery in peat soil. The research was conducted at an area with peat soil as growth media was taken from desa Rimbo Panjang Kabupaten Kampar Province of Riau by Factorial Completely Randomized Design with three replication. The first factor consists of: 0, 10, 20 and 30 (mL/polybag) of cellulolytic microorganism. The other one consists of: 2, 3 and 4 (times/day) watering. The result showed that cellulolytic microorganism with frequency of watering could improve peat soil fertility and increased growth of oil palm in pre-nursery. Use of 30 ml cellulolytic microorganism with 2 times watering/day decreased C/N ratio till 26% and increased 1–1.5 of soil pH and created the best growth of oil palm seed, is equal to standart wich is recominded by the central oil palm research of Indonesia.